The proliferation of cryopreserved bovine granulosa cells under in vitro Long-term culture - Hoang Nghia, Son; Ho Nguyen Quynh, Chi; Pham Minh, Anh; Hoang Nghia Quang, Huy; Doan Chinh, Chung; Le Thanh, Long (Academia Journal of Biology, 2026)
This study investigated the long-term proliferative potential and senescence-associated characteristics of cryopreserved bovine granulosa cells (cry-bGCs) during extended in vitro culture. The cry-bGCs demonstrated a high proliferative capacity, maintaining growth up to passage 20. However, late-passage cells (P15–P20) exhibited signs of replicative senescence, including reduced proliferation rates and increased cell cycle arrest at the G0/G1 phase. Morphometric analyses revealed significant enlargements in both nuclear and cytoplasmic areas, accompanied by the formation of thickened actin filament bundles within the cytoplasm. Furthermore, the decreased nuclear intensity in late-passage cry-bGCs suggested altered chromatin condensation and impaired DNA replication during mitosis. Progressive morphological changes, from homogenous early-passage cells to polymorphic late-passage cells, indicate cytoplasmic expansion and actin remodeling as key senescence markers. These results demonstrate that cry-bGCs possess strong proliferative potential after cryopreservation but gradually undergo replicative senescence during prolonged culture.